Integration of an Online Discussion Forum in a Campus-based Undergraduate Biology Class - Sandrine Turcotte; Thérèse Laferrière (The Canadian Network for Innovation in Education (CNIE), 2004)
This research paper describes the use of computer mediated conferencing (CMC) to support the teaching of biology to undergraduates. The use of this pedagogical innovation was a first-time experience for both the instructor and his students. The objectives of this project were to increase students' active participation, to facilitate collaborative knowledge building, and to enhance the use of the scientific approach in problemsolving activities. The data indicate that some positive results were achieved for each objective. The use of online computer conferences shows a lot of promise when it is based on reflection, problem-solving, collaborative learning and knowledge building. Internet conferencing tools support students as they reflect and work together and open doors to numerous new educational experiences for both the students and the professors.